PENGARUH PEMBELAJARAN IPS TERHADAP PENGEMBANGAN KETERAMPILAN SOSIAL SISWA MADRASAH IBTIDAIYAH SWASTA AL-FITRAH - Revi Dahlianti; Faisal Ahmad (Pelantar Press, 2026)
This study aims to understand the influence of Social Studies (IPS) learning on the development of social skills among students in Madrasah Ibtidaiyah. The research employed a qualitative descriptive approach, with data collected through observation, interviews, and documentation. The focus was directed toward how students interact during the learning process, the forms of cooperation that emerge, and the social attitudes that develop. Data analysis was conducted using an interactive model consisting of data reduction, data display, and conclusion drawing/verification. The findings indicate that Social Studies learning contributes positively to students’ social skills. Students who were initially passive and hesitant to communicate began to show behavioral changes after the teacher implemented group discussions and social simulations. They became more active in expressing opinions, listening to peers, and collaborating to complete tasks. Both teachers and students acknowledged that contextual Social Studies learning fosters tolerance, empathy, and a sense of togetherness. Thus, it can be concluded that Social Studies learning functions not only as a medium for knowledge transfer but also as an effective means of shaping the social character of Madrasah Ibtidaiyah students.